Infusing Unplugged Computational Thinking into a Probability Worksheet for Students’ Mathematical Literacy - Sari, Christina Kartika; Murtiyasa, Budi; Machromah, Isnaeni Umi; Ramadhani, Noti Armyta; Rejeki, Sri; Palupi, Retno; Yuliana, Irma (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research aims to: 1) develop a worksheet that incorporates unplugged computational thinking (CT) to support the strengthening of mathematical literacy; 2) test the validity, practicality, and effectiveness of the worksheet. Method: This study employed a development research design involving teachers, students, and experts. Data collection was conducted through literature review, observation, questionnaires, documentation, and a mathematical literacy test. Data analysis was conducted using qualitative and quantitative methods. Results: Based on the research results, the following results were obtained: 1) The CT-infused worksheet was designed to support the achievement of three learning objectives: students can determine sample points, determine probability values, and use these concepts in problem-solving; the worksheet contains learning activities that integrate CT and learning activities that support mathematical literacy; 2) The content validity index was 1, thus the worksheet is valid; Practicality tests by teachers and students yielded scores of 3.95 and 3.58, respectively, indicating that the worksheet is suitable for use as a support for mathematics learning. The trial results also demonstrated that these CT-infused worksheet is effective in improving students' mathematical literacy. Novelty: In contrast to earlier studies that focused on literature review, analysed students' CT abilities, or integrated CT into mathematics learning to improve CT abilities, this study integrates unplugged CT into a worksheet to improve junior high school students' mathematical literacy. This CT-infused worksheet has been proven valid, practical and effective as a probability teaching material to support the development of mathematical literacy.